Martian redox chemistry: oxygen reduction in low temperature magnesium perchlorate brines - Elliott, J; Ngamchuea, K; Batchelor-McAuley, C; Compton, R (American Chemical Society, 2017)
NASA has a mandate to send humans to Mars by 2033. Recent discoveries regarding Mars include the likely presence of low temperature liquid brines on the planet’s surface. This work investigates redox chemistry in near saturated aqueous 2.8 M Mg(ClO4)2 at temperatures as low as -34oC. These conditions are comparable to those thought to be found on the Martian surface. In particular electro-reduction of oxygen is studied and the diffusion coefficient and solubility of this important redox species established.